REGULATORY BENCHMARKING IN CENTRAL EUROPE: CURRENT PRACTICE AND POSSIBILITIES OF DEVELOPMENT FOR THE ENERGY SECTOR - Machek Ondrej (Annals of the University of Oradea: Economic Science, 2011)
Benchmarking is a technique of performance evaluation in which comparisons are made to benchmarks that represent external performance standards. In the field of regulation of public utilities, benchmarking can be used as an element of performance-based regulation or as a pure regulatory method, called yardstick competition. In the absence of competition, benchmarking can be used to simulate competitive pressures by comparing a regulated firm's performance against an efficient standard. The aim of this paper is to examine the Central European regulatory benchmarking practices in the energy sector, namely the electricity and natural gas distribution industries, and to analyse the possibilities of further development of regulatory benchmarking in this region. The countries onto which we focus are Czech Republic, Slovakia, Hungary, Poland, Germany, Austria and Switzerland. In the region of Central Europe there are still significant differences between countries, especially in terms of experiences in modern regulation, regulatory methods and practices, level of economic development etc. Differences are considerable especially between Western countries (Germany, Austria and Switzerland) and the countries of former Eastern Bloc (Czech Republic, Slovakia, Hungary and Poland). As a result, the degree of the use of regulatory benchmarking is also very diverse within this region. In the first part of the paper, we develop basic theoretic concepts of economic regulation. Then we describe the most frequently used regulatory methods cost-of-service regulation, incentive regulation and yardstick competitionand we deal with common regulatory benchmarking techniques, describe their principles and main challenges. Subsequenty, we provide an overview of regulatory methods and benchmarking practices for each country in the region of interest. In the final part of the paper, we analyse the challenges and possibilities for further development of regulatory benchmarking in the Central Europe. We have found that except for Switzerland, all Central European regulatory regimes are based on some form of incentive regulation. The most sophisticated methods of benchmarking are used in Germany and Austria. In these countries, benchmarking is used in both electricity and natural gas industries. The Polish regulator is using a benchmarking method in cost efficiency analysis in electricity distribution. In Hungary, a specific method of benchmarking is used. In Switzerland, no benchmarking is used at present. In Czech Republic and Slovakia, some principles of benchmarking are adopted, but not directly to the revenue requirements setting. We summarize that the possibilities for development of regulatory benchmarking in the Central Europe could be extended by reducing market concentration, unbundling large vertically integrated companies, establishing a closer cooperation with the private sector and closer harmonization of regulatory frameworks.